Role of left ventricle deformation analysis in stress echocardiography for significant coronary artery disease detection: A diagnostic study meta‐analysis. Issue 6 (22nd May 2019) - Gupta, Kartik; Kakar, Tanya S.; Gupta, Ankur; Singh, Amitoj; Gharpure, Nitin; Aryal, Sudeep; Hawi, Riem; Lloyd, Steven G.; Booker, Julian; Hage, Fadi G.; Prabhu, Sumanth D.; Nanda, Navin C.; et al.
Abstract: Background: We compared the diagnostic accuracy of longitudinal strain (LS) imaging during stress echocardiography with visual assessment of wall motion (WM) for detecting significant coronary artery disease (CAD). Methods: Our systematic search included studies reporting diagnostic measures for LS imaging and visual assessment of WM for detecting significant CAD during stress echocardiography. Summary diagnostic accuracy measures including area under the curve (AUC), sensitivity, specificity, diagnostic odds ratio (DOR), and likelihood ratios (LRs) were estimated. Results: In thirteen studies with 978 patients, ten studies used invasive coronary angiography as the reference standard. Pooled AUC for diagnosing significant CAD was 0.92 (95% confidence interval [CI] 0.89–0.94) for LS imaging as compared to 0.83 (95% CI 0.80–0.86), P  < 0.001 for visual assessment of WM. LS imaging had higher sensitivity (88% [95% CI 84–92] vs 74% [95% CI 68–80], P  < 0.001) and comparable specificity to visual assessment of WM (80% [95% CI 72–87] vs 83% [95% CI 74–90], P  = 0.592). The DOR for LS imaging and visual assessment of WM was 31 and 15, P  = 0.254, respectively. The positive LR was 4.5 for both; negative LR was 0.14 and 0.31, P  = 0.002 for LS imaging and visual assessment of WM, respectively. Conclusions: Longitudinal strain imaging during stress echocardiography has better diagnostic accuracy for detecting significant CAD as compared to visual assessment of WM. Studies using larger sample size and standardized techniques of strain measurement are required to further ascertain the added advantage of strain measurement over visual assessment alone.